Navigating Great Power Rivalry: Australia Between the United States and China - Sofia Trisni (JLAST : Journal of Law and Social Transformation, 2025)
The growing rivalry between the United States and China represents a major strategic challenge in contemporary International Relations, with significant implications for regional stability in Asia. Scholars such as Hugh White warn that the absence of a cooperative relationship between the two powers may lead to long-term instability, affecting regional actors, including Australia. Caught between its security alliance with the United States and its deep economic interdependence with China, Australia faces a complex strategic dilemma. While the United States remains Australia’s primary security partner, China has become its largest trading partner, placing Australia in a vulnerable position amid intensifying great power competition. Using a qualitative literature review, this article examines Australia’s potential role in facilitating improved US-China relations while balancing its strategic and economic interests. It argues that Australia must adopt a nuanced and proactive strategy to manage great power rivalry and safeguard its national interests